Stres Kerja Sebagai Moderasi dan Mediasi untuk Meningkatkan Komitmen yang Efektif - Luhgiatno; Paramita, Patricia Dhiana; Adhi, Daniel Kartika; Wahyuningsih, Panca (Universitas Bumigora, 2025)
Auditors working in Public Accounting Firms (KAP) face the problem of decreasing affective commitment to the organization. Increasing work stress, a high workload, and unresolved work conflicts trigger this decrease. This study aims to analyze the effects of workload and work conflict on work stress and affective commitment, and to investigate the impact of work stress on affective commitment. Addi- tionally, this study examines the role of work stress as a mediating variable in the relationship between workload and work conflict, influencing affective commitment. The type of research used is quantitative research; the population in this study consisted of auditors working in KAP in the Semarang area, to- taling 150 individuals. The sample collection method employed was purposive sampling, where sample selection was based on specific criteria determined by the researcher, resulting in 134 respondents. Data analysis techniques use Path Analysis and Moderated Regression Analysis. The results of the study indicate that work conflict has a positive and significant effect on work stress. Simultaneously, workload and work conflict also have a positive and significant effect on increasing work stress. Work stress has a negative and significant effect on auditors’ affective commitment. Work conflict has also been shown to have a negative and significant effect on affective commitment. Practical implications for the man- agement of Public Accounting Firms, particularly in efforts to maintain and improve auditors’ affective commitment through workload management, constructive conflict resolution, and work stress control in the work environment.